Inferred bi-directional interactions between vaginal microbiota, metabolome and persistent HPV infection accompanied by high-grade cervical intraepithelial neoplasia - Qin Yang; Wenkui Dai; Di Wu; Ruinan Xu; Changzhong Li; Ruifang Wu; Hui Du (BMC Microbiology)
Abstract Background Vaginal microbiota (VM) links to the risk of persistent HPV infection and the progression of cervical intraepithelial neoplasia (CIN). However, a comprehensive understanding of concurrent alterations in VM and metabolome associated with that risk remains elusive in population-based studies, particularly among Chinese women. Methods This study conducted an extensive analysis of VM and metabolome profiles in a cohort of 56 Chinese women, classified into HPV_C (natural clearance of HPV, n = 18) and HPV_PH(persistent HPV infection accompanied by high-grade CIN, n = 38), based on the result of 3–6 months follow-up visits. Results Our analysis revealed a higher prevalence of Lactobacillus-dominated samples in the HPV_C cohort. Notably, the vaginal metabolome exhibited a significant interaction with VM, with Lactobacillus emerging as a pivotal influencer. We identified 386 metabolites that significantly differentiated between HPV_C and HPV_PH groups, of which 364 were associated with VM components such as Lactobacillus, Hoylesella, Fannyhessea and Megasphaera. Further examination showed that 66 of these 364 metabolites positively correlated with Lactobacillus, including citric acid, DL-beta-Leucine, Xanoic acid and Norcholic acid. Conversely, 19 metabolites, including HPV_PH enriched maltotriose and N-Acetyl-L-aspartic acid, negatively correlated with Lactobacillus. Further analysis suggested potential bi-directional modulation between VM and persistent HPV infection accompanied by high-grade, being partially mediated by vaginal metabolites. Conclusions This study provides additional insights into the correlations between concurrent alterations in VM and metabolome associated with persistent HPV infection accompanied by high-grade CIN.